Experimental investigation of the oxidative ageing mechanisms in bitumen. (10th November 2020) - Pipintakos, Georgios; Vincent Ching, H.Y.; Soenen, Hilde; Sjövall, Peter; Mühlich, Uwe; Van Doorslaer, Sabine; Varveri, Aikaterini; Van den bergh, Wim; Lu, Xiaohu
Highlights: EPR provides evidence for carbon-centred radical formation during exposure of bitumen to oxygen. TOF-SIMS demonstrates an increase of SOx - -, HOx - -, NOx - -organics because of ageing. A fast- and a slow-rate phase for ageing can be distinguished with FTIR. EPR also shows that vanadyl-porphyrin species remain unchanged during ageing. Abstract: Oxidative ageing in bituminous materials is considered one of the most important factors for distress types in road applications. This paper aims to offer insights into the validity of commonly held beliefs regarding the oxidation phases of ageing in bitumen, the fast- and the slow-rate phase, and explore the main oxidation products formed upon ageing. In order to evaluate possible differences between bitumen types, the penetration grade as well as the bitumen production process was varied. Thus, the ageing of three different binders was first studied by Fourier-Transform Infrared (FTIR) and Electron Paramagnetic Resonance (EPR) spectroscopy. The formation of oxygen-containing molecular structures on the bitumen surface during ageing was studied with Time-of-Flight Secondary Ion Mass Spectrometry (TOF-SIMS). The results of FTIR reveal a gradual increase of sulfoxides upon ageing, while the EPR results show an increase of organic carbon-centred radicals. In parallel, TOF-SIMS results provide evidence for an increase of oxygenated compounds, such as SOx - -, HOx - - and NOx - -containing compounds. It appears also that paramagnetic metal species, such as vanadyl-porphyrins, are insusceptible during ageing. Overall, the findings of this study are in agreement with a mechanism comprising two rate-determining phases and support the formation of different oxygenated products. It is believed that the experimental approach used in this work may contribute further to an improved understanding of the ageing mechanisms in bitumen.